POLITICAL CORRUPTION AS AN EXPRESSION OF POLITICAL ALIENATION: THE RAMPANT POLITICAL CORRUPTION DURING THE DECLINE OF STATEâ IDEAL ROLE - Purnomo, Joko (Jurnal Interaktif, 2011)
Political corruption is widely omnipresent in Indonesia. Some, who are in control in government and political institutions, abuse its power in order to maximize theirÂ  self-interest in terms of wealth, power, influence, and social status. Tragically, rampant political corruption in Indonesia is becoming widespread from central to local level. This paper argues that the spread of political corruption relates to the political context in Indonesia. The significant reduction of state actions in pursuing public interest namely social justice, welfare society, and national prosperity significantly reduce public trust to the state. The absent state, then, facilitates the raise of political alienation among people. Political corruption, consequently, is conducted in order to protect self-interest of people in the era of absent state. Â Key Words: Political Corruption, absent state, political alienation